Design And Development of an Microcontroller Based Automatic Dual Axis Solar Radiation Tracker (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Global energy usage is increasing every year due to increase in world population. The need for the use of renewable energy is rapidly growing, as fossil fuels are limited. Solar energy is considered better among renewable energy sources, since it is free and readily available in abundance. Solar tracking system is one of the ways to increase efficiency. Compared to the fixed panel structure, by tracking the sun’s position and moving the solar panel in dual axis will be better. Design and development of a dual axis automatic solar radiation tracker to ensure it is always perpendicular to the sun is proposed to increase the efficiency. The Dual Axis Solar Tracker (DAST) and control system is a combination of hardware and software,   automatically track the sun’s position throughout the day time. Maximum power point tracking (MPPT) charge controller is much more efficient at certain conditions, like cloudy weather or when the intensity of light is not strong.  Light Dependant Resistor (LDR) is used to track the sun’s position by comparing the output of the sensor from the four directions (North, South, East, West). A mechanical structure developed is used for experimental studies. Dual axis movement is controlled by stepper motor with pulley and belt, while the elevation is control by a linear actuator. Static solar panel with and without MPPT charge controller and tracking solar panel with and without MPPT charge controller results are analyzed and it is proved that the solar efficiency is much improved with design developed. . It has been found that DAST provides 16% more power output compared to static solar panel.